Sociodemographic correlates of antenatal care visits in Nepal: results from Nepal Demographic and Health Survey 2016 - Mukesh Adhikari; Binaya Chalise; Bihungum Bista; Achyut Raj Pandey; Dipak Prasad Upadhyaya (BMC, 2020)
Abstract Background Good quality antenatal care visits are crucial to reduce maternal mortality and improve overall maternal and neonatal health outcomes. A previous study on antenatal care visits analyzed the nationally representative data of 2011; however, no studies have been conducted recently in Nepal. Therefore, we analyzed the sociodemographic correlates of the frequency and quality of antenatal care among Nepalese women from the nationally representative data of 2016. Methods We analyzed data obtained from the Nepal Demography Health Survey (2016) on antenatal care for 2761 women who had one or more births in the past three years. Our study defined 'good quality antenatal care' as at least a 75% score on a composite metric which was obtained by adding the weighted scores assigned to the twelve recommended components of antenatal care. We analyzed the factors associated with the frequency and quality of antenatal care by using multiple Poisson regression and multiple logistic regression. Results While 70% of the Nepalese women surveyed had at least four antenatal care visits, only 21% of these women received good-quality antenatal care. We found that the educated women (APR: 1.12; CI: 1.05-1.19) and the women of rich wealth index (APR: 1.27; CI: 1.18-1.37) were more likely to receive a higher number of antenatal visits. In contrast, women living in rural areas (APR: 0.92; CI: 0.87-0.98), and those who had more than two children (APR: 0.88; CI: 0.83-0.93) were less likely to receive a higher number of antenatal visits. Regarding the quality of antenatal care, educated women (AOR: 1.51; CI: 1.09-2.08), women who had educated husbands (AOR: 2.11; CI: 1.38-3.22), women of rich wealth index (AOR: 1.58; CI: 1.13-2.20) and women who had intended pregnancy (APR: 1.69; CI: 1.23-2.34), were more likely to receive good-quality antenatal care. Conclusions Observing a wide variation in the coverage of different components of antenatal care, concerned stakeholders could tailor the interventions by focusing on components with lower use. Because we found an association of myriad sociodemographic factors with the frequency and quality of antenatal care, targeted interventions are necessary.